PENGARUH KEPEMIMPINAN DAN K3 (KESELAMATAN DAN KESEHATAN KERJA) TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) AREA KRAMAT JATI BAGIAN TEKNIK - Hani Hajar; Apriatni Endang Prihatini (Universitas Diponegoro, 2018)
Every corporate needs resources that have an mportant influence to achieve corporate’s goal. Human resource management have a role in improving employee performance through the variables that affect itself, including leadership and OHS (Occupational Safety and Health). Based on the problem in this research, that is the decrease of employee performance of PT PLN (PERSERO) Technical Department of Kramat Jati Area in 2014 – 2016 in travo disturbance and electrical leakage that occurred. The purpose of this study is to determine the influence of leadership and OHS (Occupational Safety and Health). The type of this research is explanatory research with 44 respondents in PT PLN (PERSERO) Technical department of kramat jati area as the population. The technique of sampling using saturation sampling. Using questionnaires as data collecting technique. The data analysis conducted quantitatively with SPSS. This research conclude that leadership and occupational safety and health have postive effect on employee performance. OHS (Occupational safety and health) variable has bigger effect than leadership variable. Based to the research result, the researcher suggest that the company to pay attention of work enviroment which the work enviroment in techincal department needs collaboration for the employee to finish their job.